Knowledge, attitude and practice of blood donation among university students in Basrah, Iraq: A comparison between medical and non-medical students - Al-Asadi, Jasim N; Al-Yassen, Asaad Q. (Asian Journal of Medical Sciences, 2018)
Background: Young students can play a fundamental role in blood donation to save lives of many people. Therefore, studying factors contributing to their knowledge, attitude and practice of blood donation is essential. Aims and Objectives: To evaluate the knowledge and attitude of Basrah University students about blood donation. Materials and Methods: This descriptive cross-sectional study involved students of two colleges in Basrah University. It was carried out during the period from January to April 2017. A non-probability purposive sampling method was used in selecting the participants for this study. Information on socio-demographic characteristics, knowledge and attitude towards blood donation were collected through a structured self-administered questionnaire. Results: A total of 422 students were targeted, of these 393 (93.1%) completed the questionnaire.Only 51 (13%) of total respondents had a history of blood donation, of those 64.7% donated only once. The most mentioned reasons behind not donating were; not being asked to donate (24.6%), inconsideration of donation (11.1%), and fear of drawing blood (8.8%). Adequate knowledge was detected in 66.7% and positive attitude in 68.7%. Students of College of Medicine were younger, more knowledgeable, and donate more than those of College of Administration and Economics. Conclusion: A substantial number of the university students had inadequate blood donation knowledge. Education programs and motivational campaigns should be enhanced. Asian Journal of Medical Sciences Vol.9(6) 2018 62-67